What we do with data: A performative critique of data "collection" - Garfield Benjamin (Internet Policy Review, 2021)
Data collection is everywhere. It happens overtly and behind the scenes. It is a specific moment of legal obligation, the point at which the purpose and conditions of the data are legitimised. But what does the term data collection mean? What does it say or not say? Does it really capture the extraction or imposition taking place? How do terms and practices relate in defining the norms of data in society? This article undertakes a critique of data collection using data feminism and a performative theory of privacy: as a resource, an objective discovery and an assumption. It also discusses alternative terms and the implications of how we describe practices of 'collecting' data.
Keywords: 300; Data collection; Feminism; Queer theory; Data protection; Privacy